Growing Forward with Agricultural Policy: Strengths and Weaknesses of Canada's Agricultural Data Sets. (24th September 2013) - Poon, Kenneth; Weersink, Alfons
<x xml:space="preserve">Abstract</x> Canada has four major sources of information on the financial and production aspects of agriculture: the Census of Agriculture, the Farm Financial Survey, the Agricultural Taxation Data Program, and administrative data resulting from Business Risk Management programs. These data sets form the basis for the analysis of Canadian agricultural policy, which has shifted from a focus on farm family income enhancement, to commodity‐specific supply stabilization, to enhancing the competitiveness of the sector and individual operations. The changing focus of agricultural policy together with the growing heterogeneity of the farm sector has significant implications for the forms of analysis conducted and the suitability of the data collected for analysis. No single data set supplies all the data necessary to determine the need for and effect of farm support programs. Census data provide descriptive measures of total production but lack detailed farm financial information. Such data is provided by tax data but information is not provided on assets/liabilities, inputs/outputs, and demographics. Proposals to consider the individuals behind a unit of production in the determination of support eligibility would drive an even larger gap between data demands and the current supply of publicly provided data.